Herdabilidade de preditores do risco cardiovascular - Oliveira, Michelle Vasconcelos de (2013)
genetic and environmental factors contribute to the development of cardiovascular risk and that influence can be differentiated by factors characteristic of each population, age and sex. Aim: To investigate the heritability of anthropometric and biochemical markers as predictors of cardiovascular risk in men and women of different age groups, using the method of twins. Methods: A sample of 88 subjects and of these 52 children and adolescents (08-17 years old) 32 monozygotic (20 female and 12 male) and 20 dizygotic (12 female and 08 male) and 36 adults (18-28 years age) 24 monozygotic (08 female and 16 male) and 12 dizygotic (06 female and 06 male), living in the metropolitan region of Natal / RN, Brazil. Anthropometric measures were taken as the height, body mass, waist circumference (WC), sum of skinfolds (ΣDC), fat percentage CUN-BAE, BMI and conicity. Biochemical markers analyzed were: fasting glucose (GLU), total cholesterol (COL), HDL-C, LDL-C and triglycerides (TG). After processing the data the index of heritability (h2) = (S ² MZ) / S ² DZ (DZ S ²) X100 was applied disaggregated by sex and age. Results: The variables showed differential heritability of behavior for men and women, depending on age. The variables with the highest heritability values were ΣDC, GLU, HDL, TG, in men and BMI, WC, ΣDC, GLU, HDL-C and TG in women. And more influenced by the environment variables were: body mass, BMI, Chol, LDL-C in men; body mass and LDL-C in women. Conclusion: Differences index of heritability by gender for cardiovascular risk predictors may assist in planning specific intervention strategies according to gender and stage of life of that individual. It is from the level of environmental influence that can run interventions for changes of components related to cardiovascular risk